Positive electrode material for improving performance of LMFP battery and preparation method of positive electrode material
Modified LMFP materials were prepared through hydrothermal synthesis and calcining technology and modified the battery separator, which solved the problem of poor rate performance of LMFP batteries and significantly improved the first charge and discharge efficiency and rate performance of the battery.
Patent Information
- Application Number
- CN202510104836.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-01-23
AI Technical Summary
The rate performance of LMFP batteries is poor, which affects their application.
Modified LMFP materials were prepared by hydrothermal synthesis and calcination techniques, and the cell's separator was modified, including the use of modified Elosite nanotubes and zeolite coatings, to improve the wettability and ionic conductivity of the separator.
It significantly improves the battery's first charge and discharge efficiency and rate performance, broadens the lithium ion diffusion channel, and enhances the overall performance of the battery.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of battery preparation, in particular to a positive electrode material for improving the performance of an LMFP battery and a preparation method thereof. Background Art
[0002] In recent years, lithium iron phosphate (LFP) material has gradually occupied the domestic power battery positive electrode material market due to its advantages such as environmental protection, low cost and high safety performance. However, its application is restricted by its limited voltage platform and poor low-temperature performance.
[0003] Nowadays, the introduction of manganese has increased the voltage platform of LFP from 3.4V to 4.1V of LMFP, which is a breakthrough in voltage platform. Since Mn has a higher voltage platform and Fe has better conductivity, when the manganese-iron ratio is high, Mn drives the battery voltage and energy density to increase significantly, but its conductivity is greatly reduced, thus affecting its rate performance. Therefore, how to improve the rate performance of LMFP has become a top priority.
[0004] In summary, in order to solve the above problems, a positive electrode material for improving the performance of a LMFP battery and a preparation method thereof are provided. Summary of the invention
[0005] The object of the present invention is to provide a positive electrode material for improving the performance of a LMFP battery and a preparation method thereof, so as to solve the problems raised in the prior art.
[0006] To achieve the above object, the present invention provides the following technical solutions: A method for preparing a positive electrode material for improving the performance of a LMFP battery comprises the following steps: Step 1: Dissolve the traditional LMFP material and NaOH particles in concentrated sulfuric acid, stir evenly, transfer to a reactor, bake at 180°C for 16 hours, then filter, wash, and vacuum dry to obtain LMFP-Na; Step 2: LMFP-Na and LiF are mixed and mechanically ball-milled, and then placed in a tubular furnace and calcined at 900° C. for 10 h to obtain the positive electrode material.
[0007] More optimally, the mass ratio of the conventional LMFP material to the NaOH particles is (120-125):1; the mass ratio of the conventional LMFP material to LiF is (100-105):1.
[0008] More optimally: during the calcination process, the heating rate is 40°C / min and the annealing rate is 40°C / min.
[0009] A method for preparing a button battery comprises the following steps: (1) Mixing the positive electrode material obtained above with a binder and a conductive agent, and stirring them evenly to obtain a positive electrode slurry; (2) coating the positive electrode slurry on a 12 μm aluminum foil and drying it at 120° C. for 12 h to obtain a positive electrode sheet; (3) Assemble according to the assembly sequence of "battery shell - place positive electrode sheet - drip electrolyte - place modified diaphragm - drip electrolyte - place lithium sheet - place gasket spring - battery shell" to obtain a button battery.
[0010] More optimally: the preparation process of the modified diaphragm is: 1): Add polypropylene resin, modified halloysite nanotubes, initiator and antioxidant into a twin-screw extruder, melt-blend and extrude, cool and shape, then stretch longitudinally and transversely, shape and roll up to obtain a film; 2): The zeolite powder is dispersed in a polyvinylidene fluoride solution, and then coated on a membrane by a dip coating method to obtain a zeolite coating, and dried at room temperature to obtain a modified diaphragm.
[0011] More optimally: the preparation process of the modified halloysite nanotubes is: S1: dispersing halloysite nanotubes in methanol, ultrasonically treating for 15-20 min, then adding γ-glycidyloxypropyltrimethoxysilane dropwise, mixing, stirring at 75-80° C. for 3-4 h, to obtain epoxidized halloysite nanotubes; S2: dissolving amino-polyethylene glycol-carboxyl and amino cage-type polysilsesquioxane in chloroform, stirring with ultrasonic for 1-2 hours, adding 4-dimethylaminopyridine, heating to 60-70°C, reacting for 4-5 hours, centrifuging, washing, and vacuum drying to obtain polyethylene glycol-modified siloxane; S3: Mix polyethylene glycol-modified siloxane and L-allylglycine, add to dimethyl sulfoxide, add 4-dimethylaminopyridine, heat to 80-90° C., react for 7-8 hours, and post-treat to obtain amino-alkenyl siloxane; S4: Add amino-alkenyl siloxane and epoxidized halloysite nanotubes to tetrahydrofuran, stir vigorously for 1-2 hours, centrifuge, wash with tetrahydrofuran and deionized water, and dry the obtained powder under vacuum for 12-15 hours to obtain modified halloysite nanotubes.
[0012] More optimally: the epoxidized halloysite nanotubes include the following components: by weight, 20-25 parts of halloysite nanotubes, 150-200 parts of methanol, and 0.1-0.2 parts of γ-glycidyloxypropyltrimethoxysilane; The polyethylene glycol modified siloxane comprises the following components: by weight, 12-15 parts of amino-polyethylene glycol-carboxyl, 20-22 parts of amino cage-type polysilsesquioxane, 100-150 parts of chloroform, and 0.1-0.2 parts of 4-dimethylaminopyridine; The amino-alkenyl siloxane comprises the following components: by weight, 12-15 parts of polyethylene glycol modified siloxane, 5-6 parts of L-allylglycine, 80-100 parts of dimethyl sulfoxide, and 0.05-0.1 parts of 4-dimethylaminopyridine; The modified halloysite nanotube comprises the following components: by weight, 12-15 parts of amino-alkenyl siloxane, 8-10 parts of epoxidized halloysite nanotube, and 80-100 parts of tetrahydrofuran.
[0013] More optimally, the membrane comprises the following components: by weight, 50-60 parts of polypropylene resin, 5-8 parts of modified halloysite nanotubes, 0.1-0.2 parts of initiator, and 4-5 parts of antioxidant; the thickness of the zeolite coating is 2-4 μm.
[0014] More optimally, the membrane comprises the following components: the initiator comprises one of benzoyl peroxide and lauroyl peroxide; the antioxidant comprises one or more of hindered phenol antioxidants and thioester antioxidants.
[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention prepares the modified LMFP material through hydrothermal synthesis and calcination technology, and further modifies the battery diaphragm, effectively improving the initial charge and discharge efficiency and rate performance of the battery. The details are as follows: First, the cathode material prepared by the present invention has a larger ionic radius than the conventional LMFP material. + Located at the Li site, effectively broadening the Li + The diffusion channel improves the lithium ion transfer kinetics, thereby improving the rate performance; and compared with the O element, the F element has a stronger ionic bond form, and the FM bond has a stronger binding energy than the OM bond (M is a transition metal element). Therefore, F - The introduction of LiF is more conducive to improving the ionic conductivity of raw materials, thereby improving battery performance; at the same time, Li + It also plays a role in improving the initial charge and discharge efficiency of LMFP batteries; Second, the hollow structure of halloysite nanotubes can provide additional adsorption sites, increase the membrane's ability to absorb electrolytes, and promote the uniform distribution of lithium ions, effectively inhibiting the germination of lithium whiskers, thereby improving the battery's initial charge and discharge efficiency. However, due to the poor dispersibility and compatibility of halloysite nanotubes in the matrix, their introduction ratio is limited; Therefore, the present invention first combines a silane coupling agent with a hydroxyl group on the surface of a halloysite nanotube to obtain an epoxidized halloysite nanotube, and then uses the carboxyl group of the amino-polyethylene glycol-carboxyl group to react with the amino group of the amino cage-type polysilsesquioxane under the action of a catalyst 4-dimethylaminopyridine to obtain a polyethylene glycol-modified siloxane; then, in order to introduce a double bond, L-allylglycine is further reacted with the amino group at the other end of the polyethylene glycol-modified siloxane, and then mixed with the epoxidized halloysite nanotube, and the amino group in the molecule can react with its epoxy group to obtain a modified halloysite nanotube; Among them, the introduction of polyethylene glycol segments improves the wettability of the diaphragm. Good diaphragm wettability is conducive to the affinity between the electrolyte and the diaphragm, expands the contact surface between the diaphragm and the electrolyte, thereby increasing the ion conductivity and providing sufficient channels for ion transmission, thereby providing a smaller effective current density and increasing the rate performance of the battery; the introduction of cage-type polysilsesquioxane segments also improves the thermal stability of the diaphragm; the double bond segments can also be cross-linked with the matrix polypropylene under the action of the initiator, thereby improving the compatibility; Third, the zeolite coating can improve the wettability of the separator to the electrolyte, which is crucial to battery performance. A separator with good wettability helps fill the electrolyte during the battery assembly process, effectively retains the electrolyte, and improves the conduction efficiency of lithium ions. DETAILED DESCRIPTION
[0016] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative work shall fall within the scope of protection of the present invention.
[0017] It should be noted that the following parts are parts by weight, and the purchase manufacturers of all raw materials involved in the present invention are not subject to any special restrictions and are exemplified as follows: in the following embodiments, amino-polyethylene glycol-carboxyl CAS is 139729-28-5; the amino cage-type polysilsesquioxane product number is Q-0000177; L-allyl glycine CAS is 195316-72-4; γ-glycidyloxypropyltrimethoxysilane CAS is 2530-83-8.
[0018] Embodiment 1: A method for preparing a button battery, comprising the following steps: (1) Mixing the positive electrode material obtained above with PVDF and Super P, stirring evenly, to obtain a positive electrode slurry; (2) coating the positive electrode slurry on a 12 μm aluminum foil and drying it at 120° C. for 12 h to obtain a positive electrode sheet; (3) Assemble according to the assembly sequence of “battery shell - place positive electrode sheet - drip electrolyte - place separator (polypropylene, 20 μm) - drip electrolyte - place lithium sheet - place gasket spring - battery shell” to obtain a button battery; Among them, the preparation process of the positive electrode material is: Step 1: Dissolve the traditional LMFP material and NaOH particles in concentrated sulfuric acid, stir evenly, transfer to a reactor, bake at 180°C for 16 hours, then filter, wash, and vacuum dry to obtain LMFP-Na; Step 2: LMFP-Na and LiF are mixed and mechanically ball-milled, and then placed in a tubular furnace and calcined at 900° C. for 10 hours to obtain a positive electrode material; the mass ratio of the traditional LMFP material to the NaOH particles is 125:1; the mass ratio of the traditional LMFP material to LiF is 105:1.
[0019] Example 2: is basically the same as Example 1, except that the mass ratio of the traditional LMFP material to NaOH is 115:1.
[0020] Example 3: is basically the same as Example 1, except that the mass ratio of the traditional LMFP material to NaOH is 120:1.
[0021] Example 4: is basically the same as Example 1, except that the mass ratio of the traditional LMFP material to NaOH is 130:1.
[0022] Example 5: is basically the same as Example 1, except that the mass ratio of the traditional LMFP material to NaOH is 135:1.
[0023] Example 6: is basically the same as Example 1, except that the mass ratio of the traditional LMFP material to LiF is 95:1.
[0024] Example 7: is basically the same as Example 1, except that the mass ratio of the traditional LMFP material to LiF is 100:1.
[0025] Embodiment 8: It is basically the same as Embodiment 1, except that the mass ratio of the traditional LMFP material to LiF is 110:1.
[0026] Example 9: is basically the same as Example 1, except that the mass ratio of the traditional LMFP material to LiF is 115:1.
[0027] Comparative Example 1: Basically the same as Example 1, except that: no NaOH is introduced in step 1.
[0028] Comparative Example 2: basically the same as Example 1, except that: no LiF material is introduced in step 1.
[0029] Comparative Example 3: is basically the same as Example 1, except that: conventional LMFP is used as the positive electrode material.
[0030] Comparative Example 4: Experiments were conducted with the addition of a modified diaphragm, as follows: A method for preparing a button battery comprises the following steps: (1) Mixing the positive electrode material obtained above with PVDF and Super P, stirring evenly, to obtain a positive electrode slurry; (2) coating the positive electrode slurry on a 12 μm aluminum foil and drying it at 120° C. for 12 h to obtain a positive electrode sheet; (3) Assemble according to the assembly sequence of “battery shell - place positive electrode sheet - drip electrolyte - place modified diaphragm (polypropylene, 20 μm) - drip electrolyte - place lithium sheet - place gasket spring - battery shell” to obtain a button battery; Among them, the preparation process of the positive electrode material is: Step 1: Dissolve the traditional LMFP material and NaOH particles in concentrated sulfuric acid, stir evenly, transfer to a reactor, bake at 180°C for 16 hours, then filter, wash, and vacuum dry to obtain LMFP-Na; Step 2: LMFP-Na and LiF are mixed and mechanically ball-milled, and then placed in a tubular furnace and calcined at 900° C. for 10 hours to obtain a positive electrode material; the mass ratio of the traditional LMFP material to the NaOH particles is 125:1; the mass ratio of the traditional LMFP material to LiF is 105:1.
[0031] A preparation process of a modified diaphragm is: 1): 50 parts of polypropylene resin, 5 parts of modified halloysite nanotubes, 0.1 parts of initiator and 4 parts of antioxidant are added into a twin-screw extruder, melt-blended and extruded, cooled and shaped, and then longitudinally stretched and transversely stretched, shaped, and rolled to obtain a film; 2): Dispersing zeolite powder in a polyvinylidene fluoride solution, and then coating it on a membrane by dip coating to obtain a zeolite coating, and drying it at room temperature to obtain a modified diaphragm; The preparation process of the modified halloysite nanotubes is: S1: 20 parts of halloysite nanotubes were dispersed in 150 parts of methanol, and ultrasonically treated for 20 minutes, and then 0.1 parts of γ-glycidyloxypropyltrimethoxysilane were added dropwise, and the mixture was stirred at 80° C. for 4 hours to obtain epoxidized halloysite nanotubes; S2: Dissolve 12 parts of amino-polyethylene glycol-carboxyl and 20 parts of amino cage-type polysilsesquioxane in 100 parts of chloroform, stir ultrasonically for 2 hours, add 0.1 parts of 4-dimethylaminopyridine, heat to 70°C, react for 5 hours, centrifuge, wash, and vacuum dry to obtain polyethylene glycol-modified siloxane; S3: 12 parts of polyethylene glycol-modified siloxane and 5 parts of L-allylglycine were mixed, added to 80 parts of dimethyl sulfoxide, 0.05 parts of 4-dimethylaminopyridine were added, the temperature was raised to 90°C, the reaction was performed for 8 hours, and post-processing was performed to obtain amino-alkenyl siloxane; S4: 12 parts of amino-alkenylated siloxane and 8 parts of epoxidized halloysite nanotubes were added to 80 parts of tetrahydrofuran, stirred vigorously for 2 hours, centrifuged, washed with tetrahydrofuran and deionized water, and the obtained powder was dried under vacuum for 15 hours to obtain modified halloysite nanotubes.
[0032] Comparative Example 5: The halloysite nanotubes are not modified, and the rest is the same as Comparative Example 4, specifically as follows: A preparation process of a modified diaphragm is: 1): 50 parts of polypropylene resin, 5 parts of halloysite nanotubes and 4 parts of antioxidant are added into a twin-screw extruder, melt-blended and extruded, cooled and shaped, and then longitudinally stretched and transversely stretched, shaped, and rolled to obtain a film; 2): The zeolite powder is dispersed in a polyvinylidene fluoride solution, and then coated on a membrane by a dip coating method to obtain a zeolite coating, and dried at room temperature to obtain a modified diaphragm.
[0033] Comparative Example 6: No zeolite coating was added, and the rest was the same as Comparative Example 4, specifically as follows: A preparation process of a modified diaphragm is: 1): 50 parts of polypropylene resin, 5 parts of modified halloysite nanotubes, 0.1 parts of initiator and 4 parts of antioxidant are added into a twin-screw extruder, melt-blended and extruded, cooled and shaped, and then longitudinally stretched and transversely stretched, shaped, and rolled to obtain a modified diaphragm; The preparation process of the modified halloysite nanotubes is: S1: 20 parts of halloysite nanotubes were dispersed in 150 parts of methanol, and ultrasonically treated for 20 minutes, and then 0.1 parts of γ-glycidyloxypropyltrimethoxysilane were added dropwise, and the mixture was stirred at 80° C. for 4 hours to obtain epoxidized halloysite nanotubes; S2: Dissolve 12 parts of amino-polyethylene glycol-carboxyl and 20 parts of amino cage-type polysilsesquioxane in 100 parts of chloroform, stir ultrasonically for 2 hours, add 0.1 parts of 4-dimethylaminopyridine, heat to 70°C, react for 5 hours, centrifuge, wash, and vacuum dry to obtain polyethylene glycol-modified siloxane; S3: 12 parts of polyethylene glycol-modified siloxane and 5 parts of L-allylglycine were mixed, added to 80 parts of dimethyl sulfoxide, 0.05 parts of 4-dimethylaminopyridine were added, the temperature was raised to 90°C, the reaction was performed for 8 hours, and post-processing was performed to obtain amino-alkenyl siloxane; S4: 12 parts of amino-alkenylated siloxane and 8 parts of epoxidized halloysite nanotubes were added to 80 parts of tetrahydrofuran, stirred vigorously for 2 hours, centrifuged, washed with tetrahydrofuran and deionized water, and the obtained powder was dried under vacuum for 15 hours to obtain modified halloysite nanotubes.
[0034] Comparative Example 7: Only the silane coupling agent is used to modify the halloysite nanotubes, and the rest is the same as Comparative Example 4, as follows: A preparation process of a modified diaphragm is: 1): 50 parts of polypropylene resin, 5 parts of modified halloysite nanotubes, 0.1 parts of initiator and 4 parts of antioxidant are added into a twin-screw extruder, melt-blended and extruded, cooled and shaped, and then longitudinally stretched and transversely stretched, shaped, and rolled to obtain a film; 2): Dispersing zeolite powder in a polyvinylidene fluoride solution, and then coating it on a membrane by dip coating to obtain a zeolite coating, and drying it at room temperature to obtain a modified diaphragm; The preparation process of the modified halloysite nanotubes is: S1: 20 parts of halloysite nanotubes were dispersed in 150 parts of methanol, and ultrasonically treated for 20 minutes. Then, 0.1 parts of γ-glycidyloxypropyltrimethoxysilane were added dropwise, and the mixture was stirred at 80° C. for 4 hours to obtain epoxidized halloysite nanotubes.
[0035] Testing experiment: (1) The button battery was charged and discharged at 0.1C current using a button battery charge and discharge tester (Wuhan Blue Electric, CT2001A) with a voltage range of 2.5-4.1V. The button battery was charged and discharged at different rates (0.5C, 1C, 2C) using a button battery charge and discharge tester (Wuhan Blue Electric, CT2001A), with a voltage range of 2.5-4.1V. The data obtained are shown in the following table: Table 1
[0036] Conclusion: Example 1 prepared the positive electrode material by hydrothermal synthesis and calcination technology, which effectively improved the initial charge and discharge efficiency and rate performance of the battery. Comparative Example 4, on this basis, added a modified diaphragm to further improve the initial charge and discharge efficiency and rate performance of the battery. It is in line with practical applications.
[0037] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a positive electrode material for improving the performance of a LMFP battery, characterized in that: The following steps are involved: Step 1: Dissolve the traditional LMFP material and NaOH particles in concentrated sulfuric acid, stir evenly, transfer to a reactor, bake at 180-120°C for 16-18h, then filter, wash, and vacuum dry to obtain LMFP-Na; Step 2: LMFP-Na and LiF are mixed and mechanically ball-milled, and then placed in a tubular furnace and calcined at 900-950° C. for 10-12 hours to obtain a positive electrode material.
2. The method for preparing a positive electrode material for improving the performance of a LMFP battery according to claim 1, characterized in that: The mass ratio of the traditional LMFP material to the NaOH particles is (120-125):1; the mass ratio of the traditional LMFP material to LiF is (100-105):
1.
3. The method for preparing a positive electrode material for improving the performance of a LMFP battery according to claim 1, characterized in that: During the calcination process, the heating rate is 40-45°C / min, and the annealing rate is 40-45°C / min.
4. A positive electrode material, characterized in that: The positive electrode material is obtained by the preparation method described in claim 1.
5. A method for preparing a button battery, characterized in that: The following steps are involved: (1) Mixing the positive electrode material according to claim 4 with a binder and a conductive agent, and stirring them evenly to obtain a positive electrode slurry; (2) coating the positive electrode slurry on a 12-15 μm aluminum foil and drying at 120-130° C. for 12-15 hours to obtain a positive electrode sheet; (3) Assemble according to the assembly sequence of "battery shell - place positive electrode sheet - drip electrolyte - place modified diaphragm - drip electrolyte - place lithium sheet - place gasket spring - battery shell" to obtain a button battery.
6. The method for preparing a button battery according to claim 5, characterized in that: The preparation process of the modified diaphragm is as follows: 1): Add polypropylene resin, modified halloysite nanotubes, initiator and antioxidant into a twin-screw extruder, melt-blend and extrude, cool and shape, then stretch longitudinally and transversely, shape and roll up to obtain a film; 2): The zeolite powder is dispersed in a polyvinylidene fluoride solution, and then coated on a membrane by a dip coating method to obtain a zeolite coating, and dried at room temperature to obtain a modified diaphragm.
7. The method for preparing a button battery according to claim 6, characterized in that: The preparation process of the modified halloysite nanotubes is: S1: dispersing halloysite nanotubes in methanol, ultrasonically treating for 15-20 min, then adding γ-glycidyloxypropyltrimethoxysilane dropwise, mixing, stirring at 75-80° C. for 3-4 h, to obtain epoxidized halloysite nanotubes; S2: dissolving amino-polyethylene glycol-carboxyl and amino cage-type polysilsesquioxane in chloroform, stirring with ultrasonic for 1-2 hours, adding 4-dimethylaminopyridine, heating to 60-70°C, reacting for 4-5 hours, centrifuging, washing, and vacuum drying to obtain polyethylene glycol-modified siloxane; S3: Mix polyethylene glycol-modified siloxane and L-allylglycine, add to dimethyl sulfoxide, add 4-dimethylaminopyridine, heat to 80-90° C., react for 7-8 hours, and post-treat to obtain amino-alkenyl siloxane; S4: Add amino-alkenyl siloxane and epoxidized halloysite nanotubes to tetrahydrofuran, stir vigorously for 1-2 hours, centrifuge, wash with tetrahydrofuran and deionized water, and dry the obtained powder under vacuum for 12-15 hours to obtain modified halloysite nanotubes.
8. The method for preparing a button battery according to claim 7, characterized in that: The epoxidized halloysite nanotubes include the following components: 20-25 parts by weight of halloysite nanotubes, 150-200 parts by weight of methanol, and 0.1-0.2 parts by weight of γ-glycidyloxypropyltrimethoxysilane; The polyethylene glycol modified siloxane comprises the following components: by weight, 12-15 parts of amino-polyethylene glycol-carboxyl, 20-22 parts of amino cage-type polysilsesquioxane, 100-150 parts of chloroform, and 0.1-0.2 parts of 4-dimethylaminopyridine; The amino-alkenyl siloxane comprises the following components: by weight, 12-15 parts of polyethylene glycol modified siloxane, 5-6 parts of L-allylglycine, 80-100 parts of dimethyl sulfoxide, and 0.05-0.1 parts of 4-dimethylaminopyridine; The modified halloysite nanotube comprises the following components: by weight, 12-15 parts of amino-alkenyl siloxane, 8-10 parts of epoxidized halloysite nanotube, and 80-100 parts of tetrahydrofuran.
9. The method for preparing a button battery according to claim 6, characterized in that: The membrane comprises the following components: by weight, 50-60 parts of polypropylene resin, 5-8 parts of modified halloysite nanotubes, 0.1-0.2 parts of initiator, and 4-5 parts of antioxidant; the thickness of the zeolite coating is 2-4 μm.
10. The method for preparing a button battery according to claim 9, characterized in that: The membrane comprises the following components: the initiator comprises one of benzoyl peroxide and lauroyl peroxide; and the antioxidant comprises one or more of hindered phenol antioxidants and thioester antioxidants.
Citation Information
Patent Citations
Method for preparing lithium manganese iron phosphate from lithium iron phosphate
CN109264691A
Lithium iron phosphate positive electrode material and preparation method thereof
CN109888282A
Method for regenerating anode waste material of scrapped lithium iron phosphate battery
CN113651305A
Positive electrode material and preparation method thereof, positive electrode plate and battery
CN116646492A
Lithium ion battery diaphragm with modified ceramic coating
CN118712663A